2013
DOI: 10.1016/j.jobcr.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Salivary defense system alters in vegetarian

Abstract: a b s t r a c tPurpose: The aim of this research was investigating antimicrobial and enzymatic antioxidant activities in salivary fluids of vegetarians as compared to normal subjects.Material & Methods: Antimicrobial activity of the saliva samples was evaluated against four clinically important bacteria. The biological activities of three of the main antioxidant enzymes of saliva were measured using appropriate methods of enzyme assay in both groups.Results: According to the results, saliva obtained from veget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
4
0
2
Order By: Relevance
“…However, several studies investigated catalase activity in saliva. A significant increase in activity of catalase, superoxide dismutase and peroxidase was found in saliva of young women after one month course of aerobic training [66] , while decreased activity of the three antioxidant enzymes was reported in vegetarians [67] . We believe that salivary catalase in women is a part of intrinsic antioxidant defense.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies investigated catalase activity in saliva. A significant increase in activity of catalase, superoxide dismutase and peroxidase was found in saliva of young women after one month course of aerobic training [66] , while decreased activity of the three antioxidant enzymes was reported in vegetarians [67] . We believe that salivary catalase in women is a part of intrinsic antioxidant defense.…”
Section: Discussionmentioning
confidence: 99%
“…4 Salivary fluid protects the oral cavity against detritus agents such as microorganisms, toxins and various oxidants. 5 We have previously found that the biochemistry of human saliva is altered in response to external and internal factors such as smoking, 6 vegetarian diet, 7 peptic ulcer 8 and Ramadan fasting. 9 Other investigators have shown that in vitro exposure to cigarette smoke could significantly decrease biological activity of some enzymes, both in plasma and in saliva.…”
Section: Introductionmentioning
confidence: 99%
“…The peculiar saliva features, firstly, deal with its obligatory presence in the oral cavity, and saliva always participates in the sensory perception of food. Secondly, salivary flow rate and composition are flexibly regulated in response to food stimuli [34] and are also determined by the individual characteristics of a person (age [40,41,42], sex [43], diet [58,59,60], physiological state [44]). Thirdly, saliva affects taste, aroma, and texture perception, thanks to its composition and properties.…”
Section: Discussionmentioning
confidence: 99%
“…All these aspects should be carefully controlled in the design of the food perception studies ages [40][41][42], sex [43], and health status [44]. Moreover, the salivary composition and secretion change in the same individual during the day and display circadian variation [45][46][47][48][49], just as it may change owing to physical activity [48,[50][51][52][53][54][55][56][57], and depend on the diet [58][59][60]. In view of the influences of the aforementioned factors, the perception of food during oral processing is determined not only by the salivation, which is adjusted in response to a specific food product, but also by the composition of unstimulated saliva.…”
Section: Saliva Types and Salivationmentioning
confidence: 99%